Defective Neuronal Positioning Correlates With Aberrant Motor Circuit Function in Zebrafish - Asante, Emilia; Hummel, Devynn; Gurung, Suman; Kassim, Yasmin M.; Al-Shakarji, Noor; Palaniappan, Kannappan; Sittaramane, Vinoth; Chandrasekhar, Anand (Frontiers in Neural Circuits, 2021)
Precise positioning of neurons resulting from cell division and migration during development is critical for normal brain function. Disruption of neuronal migration can cause a myriad of neurological disorders. To investigate the functional consequences of defective neuronal positioning on circuit function, we studied a zebrafish frizzled3a (fzd3a) loss-of-function mutant off-limits (olt) where the facial branchiomotor (FBM) neurons fail to migrate out of their birthplace. A jaw movement assay, which measures the opening of the zebrafish jaw (gape), showed that the frequency of gape events, but not their amplitude, was decreased in olt mutants. Consistent with this, a larval feeding assay revealed decreased food intake in olt mutants, indicating that the FBM circuit in mutants generates defective functional outputs. We tested various mechanisms that could generate defective functional outputs in mutants. While fzd3a is ubiquitously expressed in neural and non-neural tissues, jaw cartilage and muscle developed normally in olt mutants, and muscle function also appeared to be unaffected. Although FBM neurons were mispositioned in olt mutants, axon pathfinding to jaw muscles was unaffected. Moreover, neuromuscular junctions established by FBM neurons on jaw muscles were similar between wildtype siblings and olt mutants. Interestingly, motor axons innervating the interhyoideus jaw muscle were frequently defasciculated in olt mutants. Furthermore, GCaMP imaging revealed that mutant FBM neurons were less active than their wildtype counterparts. These data show that aberrant positioning of FBM neurons in olt mutants is correlated with subtle defects in fasciculation and neuronal activity, potentially generating defective functional outputs.